PENINGKATAN EKONOMI MASYARAKAT MELALUI BUDIDAYA AYAM KAMPUNG UNGGUL BALITBANGTAN (KUB) DI DUSUN BONEN BAUMATA, KECAMATAN TAEBENU - Nitbani, Heny; Maha, Inggrid Trinidad; Amalo, Filphin Adolfin; Laut, Meity Marviana; Ndaong, Nemay Anggadewi (Universitas Nusa Cendana, 2023)
Community service activities are a form of actualization of the academic community's social responsibility and concern for the problems faced by the wider community. One form of this activity includes community assistance to expand knowledge and improve skills in order to improve living standards. This community service activity in Bonen Hamlet, Baumata Village, Taebenu District aims to provide assistance to PKK women regarding intensive and modern management of KUB chicken farms. The methods used in this service activity include building cages, counseling, handing over KUB chicken seeds, feed and cage equipment, as well as community assistance and ongoing monitoring. The conclusion obtained is an increase in community knowledge and skills regarding the advantages of raising KUB chickens, business opportunities for cultivating KUB chickens, management of the care and health of KUB chickens, as well as partner groups having sustainable entrepreneurial capital.